An appraisal of mechanisms for municipal solid waste disposal and management in Nigeria (2017)
The Nigerian environment is faced with plethora of challenges of varying degrees which have continued to degrade the environment with concomitant health impact to Nigerians. For instance, the problem of improper waste disposal in Nigerian environment cut across all types of waste as well as strata of Nigerian society. It is common sight in Nigeria today to see heaps of festering waste dumps in our urban cities and commercial centres, residential apartments, the drains, the highways, corners of major or and minor streets and undeveloped plots of land. This paper seeks to appraise the mechanisms for municipal solid waste disposal and management in Nigeria. The pertinent issues which the paper will interrogate include the patterns and categories of municipal solid waste in Nigeria, the environmental and health impact of waste and the mechanism for waste disposal and management in Nigeria. The paper relies on a desktop study approach; hence information were obtained from previous publication relevant to the current study, particularly from peer reviewed publications. The paper reveals indiscriminate disposal of municipal solid wastes and attendant blockage of drainage channels and flooding of the environment during and after rainfall. The impacts of this include physical nuisance of the environment and hazards to humans' health. The paper concludes with suggestions, amongst others, that government should make concerted efforts to improve the extant waste disposed and management mechanism by strengthening solid waste management infrastructural in Nigeria.